Influence of the Antiretroviral Regimen on the Early Changes in Plasma HIV RNA and Immune Activation at Initiation of Antiretroviral Therapy in Naïve HIV-1–Infected Patients. (15th April 2021) - Samri, Assia; Chalouni, Mathieu; Blanco, Julià; Behrens, Georg; Kelleher, Peter; Massanella, Marta; Ahmad, Fareed; Clotet, Bonaventura; Plettenberg, Andreas; Katlama, Christine; Richert, Laura; Raffi, François; et al.
Abstract : Supplemental Digital Content is Available in the Text.